CONDITIONS UNDERLYING THE REGIONAL DIVERSITY OF THE AREA STRUCTURE OF FARMS IN POLAND - Marks-Bielska, Renata (Acta Scientiarum Polonorum. Oeconomia, 2016)
The aim of this study has been to identify the conditions underlying the regional diversity in the area structure of farms in Poland. There are many causes of such diversity, including historical reasons, the state transformation (understood as an institutional change), availability of farmland previously owned by state farms in each of the Polish provinces, integration with the European Union (agricultural policy, also as part of the CAP), and the multifunctional use of farmland (as a production factor, a wildlife asset, a cultural and symbolic value of the landscape). In 2014, a more 30% of agricultural land in Poland was in larger farms (over 50 ha in size). However, the number of such farms is growing, which is a positive development. In the context of the amended Act on shaping the agricultural system, it can be predicted that changes in the area structure of farms will proceed towards improvement, especially by land lease agreements.